Broadband: Bringing Home the Bits - National Research Council (The National Academies Press, 2002)
Broadband communication expands our opportunities for entertainment, e-commerce and work at home, health care, education, and even e-government. It can make the Internet more useful to more people. But it all hinges on higher capacity in the "first mile" or "last mile" that connects the user to the larger communications network. That connection is often adequate for large organizations such as universities or corporations, but enhanced connections to homes are needed to reap the full social and economic promise.
Keywords: Computers and Information Technology

The Role of Advanced Computation, Predictive Technologies, and Big Data Analytics Related to Food and Nutrition Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Food and Nutrition Board hosted a hybrid public workshop in October 2023 to explore opportunities and challenges related to applying advanced computation, big data analytics, and high-performance computing, including artificial intelligence, machine learning, and deep learning, to support advances in food systems and nutrition research. Speakers discussed the appropriate use of evidence generated from these methods to inform food- and nutrition-related programs and policies.
Keywords: Food and Nutrition; Computers and Information Technology

Critical Issues in NASA Information Systems: Final Report to the National Aeronautics and Space Administration (The National Academies Press, 1987)

Computing, Communication, and the Information Age - Hopcroft, John E. (The National Academies Press, 1994)

Intellectual Property Issues in Software - National Research Council (The National Academies Press, 1991)
Software is the product of intellectual creativity, but protection of the intellectual property residing in software is the subject of some controversy. This book captures a wide range of perspectives on the topic from industry, academe, and government, drawing on information presented at a workshop and forum.
Keywords: Computers and Information Technology

Computers, Communications, and Public Policy: Report of a Workshop at Woods Hole, Massachusetts, August 14-18, 1978 - National Research Council (The National Academies Press, 1981)
Keywords: Computers and Information Technology

Design and Construction of Deep Underground Basing Facilities for Strategic Missiles: Report of a Workshop Conducted by the U.S. National Committee on Tunneling Technology, Commission on Engineering and Technical Systems, National Research Council. - National Research Council (The National Academies Press, 1982)
Keywords: Computers and Information Technology

Telecommunications Research in the United States and Selected Foreign Countries: a Preliminary Survey. Report to the National Science Foundation - National Academy of Engineering (The National Academies Press, 1973)
Keywords: Computers and Information Technology

Virtual Reality: Scientific and Technological Challenges - National Research Council (The National Academies Press, 1995)
Despite widespread interest in virtual reality, research and development efforts in synthetic environments (SE)—the field encompassing virtual environments, teleoperation, and hybrids—have remained fragmented. Virtual Reality is the first integrated treatment of the topic, presenting current knowledge along with thought-provoking vignettes about a future where SE is commonplace. This volume discusses all aspects of creating a system that will allow human operators to see, hear, smell, taste, move about, give commands, respond to conditions, and manipulate objects effectively in a real or virtual environment. The committee of computer scientists, engineers, and psychologists on the leading edge of SE development explores the potential applications of SE in the areas of manufacturing, medicine, education, training, scientific visualization, and teleoperation in hazardous environments. The committee also offers recommendations for development of improved SE technology, needed studies of human behavior and evaluation of SE systems, and government policy and infrastructure.
Keywords: Computers and Information Technology; Conflict and Security Issues

Emerging Needs and Opportunities for Human Factors Research - National Research Council (The National Academies Press, 1995)
This book identifies areas that represent new needs and opportunities for human factors research in the coming decades. It is forward-looking, problem oriented, and selectively focused on national or global problems, including productivity in organizations, education and training, employment and disabilities, health care, and environmental change; technology issues, including communications technology and telenetworking, information access and usability, emerging technologies, automation, and flexible manufacturing, and advanced transportation systems; and human performance, including cognitive performance under stress and aiding intellectual work.
Keywords: Behavioral and Social Sciences; Computers and Information Technology

A 21st Century Cyber-Physical Systems Education - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Cyber-physical systems (CPS) are "engineered systems that are built from, and depend upon, the seamless integration of computational algorithms and physical components." CPS can be small and closed, such as an artificial pancreas, or very large, complex, and interconnected, such as a regional energy grid. CPS engineering focuses on managing inter- dependencies and impact of physical aspects on cyber aspects, and vice versa. With the development of low-cost sensing, powerful embedded system hardware, and widely deployed communication networks, the reliance on CPS for system functionality has dramatically increased. These technical developments in combination with the creation of a workforce skilled in engineering CPS will allow the deployment of increasingly capable, adaptable, and trustworthy systems.
Keywords: Computers and Information Technology

The Unpredictable Certainty: Information Infrastructure Through 2000 - National Research Council (The National Academies Press, 1996)
We have available an impressive array of information technology. We can transmit literature, movies, music, and talk. Government, businesses, and individuals are eager to go on-line to buy, sell, teach, learn, and more. How, then, should we go about developing an infrastructure for on- line communication among everyone everywhere? The Unpredictable Certainty explores the national information infrastructure (NII) as the collection of all public and private information services. But how and when will the NII become a reality? How will more and better services reach the home, small businesses, and remote locations? The Unpredictable Certainty examines who will finance the NII, exploring how technology companies decide to invest in deployment and the the vain search for "killer apps" (applications that drive markets). It discusses who will pay for ongoing services and how they will pay, looking at past cost/price models relevant to the future. The Unpredictable Certainty discusses the underlying technologies, appliances, and services needed before the NII becomes a reality; reviews key features of important technologies; and analyzes current levels of deployment in telephone, cable and broadcast television, and wireless systems, and the difficulties in interconnection. The volume explores the challenge of open interfaces that stimulate new applications but also facilitate competition, the trend toward the separation of infrastructure from specific services, the tension between mature services and new contenders, the growth of the Internet, and more. The roles governments at different levels might play in fostering NII deployment are outlined, including R&D and the use of information infrastructure for better delivery of government services and information.
Keywords: Computers and Information Technology

Global Networks and Local Values: A Comparative Look at Germany and the United States - National Research Council (The National Academies Press, 2001)
Whether you call it the third wave, the information revolution, or the virtually connected world, the implications of a global information network are profound. As a society, we want to forestall the possible negative impacts without closing the door to the potential benefits. But how?
Keywords: Computers and Information Technology

Getting Up to Speed: The Future of Supercomputing - National Research Council (The National Academies Press, 2005)
Supercomputers play a significant and growing role in a variety of areas important to the nation. They are used to address challenging science and technology problems. In recent years, however, progress in supercomputing in the United States has slowed. The development of the Earth Simulator supercomputer by Japan that the United States could lose its competitive advantage and, more importantly, the national competence needed to achieve national goals. In the wake of this development, the Department of Energy asked the NRC to assess the state of U.S. supercomputing capabilities and relevant R&D. Subsequently, the Senate directed DOE in S. Rpt. 107-220 to ask the NRC to evaluate the Advanced Simulation and Computing program of the National Nuclear Security Administration at DOE in light of the development of the Earth Simulator. This report provides an assessment of the current status of supercomputing in the United States including a review of current demand and technology, infrastructure and institutions, and international activities. The report also presents a number of recommendations to enable the United States to meet current and future needs for capability supercomputers.
Keywords: Computers and Information Technology

Avoiding Surprise in an Era of Global Technology Advances - National Research Council (The National Academies Press, 2005)
The global spread of science and technology expertise and the growing commercial access to advanced technologies with possible military application are creating potentially serious threats to the technological superiority underpinning U.S. military strength. Key to dealing with this situation is the ability of the U.S. intelligence community to be able to provide adequate and effective warning of evolving, critical technologies. To assist in performing this task, the Technology Warning Division of the Defense Intelligence Agency (DIA) asked the National Research Council (NRC) to undertake a study examining technology warning issues. This report provides the first part of that study. It presents an assessment of critical, evolving technologies; postulates ways potential adversaries could disrupt these technologies; and provides indicators for the intelligence community to determine if such methods are under development. The intention of this report is to establish the foundation for a long-term relationship with the technology warning community to support the examination of technology warning issues.
Keywords: Computers and Information Technology

Computing Research for Sustainability - National Research Council (The National Academies Press, 2012)
A broad and growing literature describes the deep and multidisciplinary nature of the sustainability challenges faced by the United States and the world. Despite the profound technical challenges involved, sustainability is not, at its root, a technical problem, nor will merely technical solutions be sufficient. Instead, deep economic, political, and cultural adjustments will ultimately be required, along with a major, long-term commitment in each sphere to deploy the requisite technical solutions at scale.
Keywords: Computers and Information Technology

The Unpredictable Certainty: White Papers - National Research Council (The National Academies Press, 1997)
This book contains a key component of the NII 2000 project of the Computer Science and Telecommunications Board, a set of white papers that contributed to and complements the project's final report, The Unpredictable Certainty: Information Infrastructure Through 2000, which was published in the spring of 1996. That report was disseminated widely and was well received by its sponsors and a variety of audiences in government, industry, and academia. Constraints on staff time and availability delayed the publication of these white papers, which offer details on a number of issues and positions relating to the deployment of information infrastructure.
Keywords: Computers and Information Technology

Embedded, Everywhere: A Research Agenda for Networked Systems of Embedded Computers - National Research Council (The National Academies Press, 2001)
Advances in the miniaturization and networking of microprocessors promise a day when networked computers are embedded throughout the everyday world. However, our current understanding of what such systems would be like is insufficient to bring the promise to reality. Embedded, Everywhere explores the potential of networked systems of embedded computers and the research challenges arising from embedding computation and communications technology into a wide variety of applications—from precision agriculture to automotive telematics to defense systems. It describes how these emerging networks operate under unique constraints not present in more traditional distributed systems, such as the Internet. It articulates how these networks will have to be dynamically adaptive and self-configuring, and how new models for approaching programming and computation are necessary. Issues relating to trustworthiness, security, safety, reliability, usability, and privacy are examined in light of the ubiquitous nature of these systems. A comprehensive, systems-oriented research agenda is presented, along with recommendations to major federal funding agencies.
Keywords: Computers and Information Technology

Information Technology Innovation: Resurgence, Confluence, and Continuing Impact - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Information technology (IT) is widely understood to be the enabling technology of the 21st century. IT has transformed, and continues to transform, all aspects of our lives: commerce and finance, education, energy, health care, manufacturing, government, national security, transportation, communications, entertainment, science, and engineering. IT and its impact on the U.S. economy—both directly (the IT sector itself) and indirectly (other sectors that are powered by advances in IT)—continue to grow in size and importance.
Keywords: Computers and Information Technology

The Changing Nature of Telecommunications/Information Infrastructure - National Research Council (The National Academies Press, 1995)
Advancement of telecommunications and information infrastructure occurs largely through private investment. The government affects the rate and direction of this progress through regulation and public investment. This book presents a range of positions and perspectives on those two classes of policy mechanism, providing a succinct analysis followed by papers prepared by experts in telecommunications policy and applications.
Keywords: Computers and Information Technology